New Formula of conversion the results in olympic weightlifting - Haleczko, A. (Journal of Kinesiology and Exercise Sciences, 2014)
Introduction. The article is a complement to the preliminary report published in No 65 of Antropomotoryka in which the rules of conversion of results in women weight categories up to 75 kg and in men categories up to 105 kg were presented. Now it is the turn to do the same for categories +75 and +105 kg. Using the example given by Cleather the need of result conversion of the weightlifter`s results from these categories was presented. Currently used formulas of conversion like these by Wilks and Sinclair as well as very interesting but complicated Siff`s procedure were discussed. The last however has not found widespread use. Aim. Description of formula of conversion the Olympic weightlifting results in women categories +75 kg and men categories +105 kg. Material and methods. The material comprise the body weight data and the results of 199 women and 272 men participating in 2006-2013 in weightlifting competitions of the highest level. Due to the low relationship between body weight and result in these groups of lifters the formulas with three variables could not be used. In this situation, formulas were developed on the basis of rank lists and tables which cover the collected material. Because it does not allow the use of formulas closely describing the relationship between body weight and the achievements of lifters, particular attention was paid to the results of outstanding competitors to make that they have been properly evaluated.. Results. The effectiveness of the conversion by the new formula was evaluated with use of previously adopted criterion - the variability coefficient. Of course, its value was much higher than that obtained in the lighter categories. Comparisons with conversion formula by Sinclair were made based on the classification of lifters according to both methods of conversion and establishing the differences between extreme results. Such comparison showed the similarity of the evaluation by these two methods, like in categories up to 75 kg and 105 kg, however AT the same time proved that the new formula occured to be more accurate. Major difficulties of interpretation provided the thirteen weightlifters closing the rank list, who get high results, but the body weight of the lightest of them had exceeded 157 kg. Such relationships are difficult to explain and raise doubts in the literature in the field of competitive sports. Steady progress in the methods of evaluation of the body composition can bring in the future, in such cases, the solution purifying lifter with suspicion (of use some illegal agents). Conclusions. The new three-variable formula described in the preliminary reference, supplemented in this publication by formulas with two variables, is a qualitative leap in leveling the Olympic weightlifting results and allows an objective selection of the best lifter and reliable determination of the place of the team.